A study on the mechanism affecting the Innovation and Entrepreneurship Ability of medical students based on Constructivist Theory: mediating role of Innovation and Entrepreneurship Willingness - Pan, Hongxu; Jiang, Yujia; Huang, Yu; Zhang, Zhihao; Du, Junjie; Song, Xuejin; Zhu, Jianjun; Xie, Yanlin; Xu, Chenchen; Li, Yong (Frontiers in Medicine, 2025)
BackgroundMass Innovation and Entrepreneurship (IE) have become a global trend, yet medical education systems often fail to meet students’ innovation development needs. This study examines how universities can enhance medical students’ IE Willingness and ability.MethodsBy analyzing survey data from 1,467 medical students under Constructivist Theory, we employed Amos 23.0 and SPSS 29.1 for cross-sectional path analysis. The study measured latent constructs—IE recognition, training courses, research talent models, incentive mechanisms, willingness, and ability—through 36 observed variables.ResultsThe analysis revealed highly significant direct effects on IE Willingness from the Research Talent Training Models (β = 0.857), IE Incentive Mechanism (β = 0.731), innovation courses (β = 0.696), and IE recognition (β = 0.521). For mediation effects on IE Ability (via willingness), only IE recognition (β = 0.122) and incentive mechanisms (β = 0.064) showed significance, while research models (β = 0.053) and innovation courses (β = 0.062) were non-significant. These findings suggest that optimizing incentive mechanisms, refining innovation courses, and strengthening research talent models—the most impactful driver—can effectively foster medical students’ innovation engagement.